Toothpick test: a methodology for the detection of RR soybean plants - Silva, Fabiana Mota da [UNESP]; Uneda-Trevisoli, Sandra Helena [UNESP]; Villela, Otavia Tiago [UNESP]; Perecin, Dilermando [UNESP]; Di Mauro, Antonio Orlando [UNESP] (Univ Federal Ceara, Dept Geol, 2015)
Due to the large increase in the area cultivated with genetically modified soybean in Brazil, it has become necessary to determine methods that are fast and efficient for detecting these cultivars. The aim of this work was to test the efficiency of the toothpick method in the detection of RR soybean plants, as well as to distinguish between cultivars, for sensitivity caused by herbicide. Ten transgenic soybean cultivars, resistant to the active ingredient glyphosate, and ten conventional soybean cultivars were used. Toothpicks soaked in glyphosate were applied to all the plants at stage V6 and evaluations were made at 2, 4, 6, 8 and 10 days after application (DAA). The effects of the glyphosate on the cultivars, and the symptoms of phytotoxicity caused in the transgenic plants were evaluated by means of grading scales. The toothpick test is effective in identifying RR soybean cultivars and also in separating them into groups by sensitivity to the symptoms caused by the glyphosate.

Devido ao grande aumento da área cultivada com soja geneticamente modificada no Brasil, faz-se necessária a determinação de métodos que sejam rápidos e eficientes na detecção dessas cultivares. O objetivo deste trabalho foi testar a eficiência do método do palito na detecção de plantas de soja RR, bem como distinguir as cultivares quanto à sensibilidade causada pelo herbicida. Foram utilizadas dez cultivares de soja transgênica, resistentes ao ingrediente ativo glifosato, e dez cultivares de soja convencional. Palitos de dente embebidos em glifosato foram aplicados em todas as plantas em estádio V6 e as avaliações foram realizadas aos 2; 4; 6; 8 e 10 dias após a aplicação (DAA). Os efeitos da ação do glifosato nas cultivares e os sintomas de fitotoxicidade, ocasionados nas plantas transgênicas, foram avaliados por meio de escalas de notas. O teste do palito é eficiente para identificar as cultivares de soja RR e, além disso, separálas em grupos de sensibilidade aos sintomas causados pelo glifosato.
Teste do palito: metodologia para detecção de plantas de soja RR
Keywords: Glycine max; Phytotoxicity; Glyphosate; Toothpick method; Herbicide; Glycine max; Fitotoxidade; Glifosato; Método do palito; Herbicida